R Reengineering Produksi Pegangan Rantang Soto Guna Meningkatkan Produktivitas Pembuatan Rantang Soto di UD. Gadjah Delta - Murnawan, Hery; Setiawan, Oky Rachmad (TEKNIKA, 2023)
Gadjah Delta Company produces several kitchen utensils, especially pots, baskets, and boilers. The superior product of the three products is the 16 cm diameter soto rantang. However, there are problems in the production process of the soto rantang grip components, which are indicated that there are 2 processes that are often problematic, namely punching and cutting the end of the soto rantang handle. The yield of rejected products in both processes is quite high, reaching 2% - 3%. This is suspected by the use of machines that are still manual for both processes. The purpose of this research is to reduce the percentage of disability, increase productivity, and be able to reduce employee fatigue levels through changing the use of manual punch machines to mechanical punch machines owned by restored companies. In order to achieve the existing goals, the mechanical machine will be supported by punches and punches and punch and cut new machines from reenggineering to streamline the process of the two manual punch machines into 1 process, and make a machine seat table using anthropometric measures of the labor body. This study used reengineering, anthropometry, and Cardiovascular Load (%CVL) methods, resulting in an increase in productivity reaching 90% without rejection results, as well as a decrease in labor fatigue levels reaching 19.5% from the previous condition.